Contemporary sequential segmental approach to congenital heart disease using four-dimensional magnetic resonance imaging with ferumoxytol: an illustrated editorial - Yoo, Shi-Joon; Perens, Gregory; Nguyen, Kim-Lien; Yoshida, Takegawa; Saprungruang, Ankavipar; Van Arsdell, Glen S.; Finn, J. Paul (Frontiers in Cardiovascular Medicine, 2023)
The ferumoxytol-enhanced 4D MR angiography with MUSIC (Multiphase Steady State Imaging with Contrast) technique provides a single data set that captures dynamic cardiovascular anatomy and ventricular function at the same time. Homogeneous opacification of all cardiovascular structures within the imaging volume allows full sequential segmental approach to the congenital heart diseases without any blind spots. The complex systemic and pulmonary venous anatomy is particularly well captured in the MUSIC. Cinematographic display of multiplanar sectional and 3D volume images is helpful in the morphological identification of the cardiac chambers, the assessment of the dynamic nature of the ventricular outflow tracts, and the assessment of the coronary arterial origins and courses.